Beruházások szerkezetének vizsgálata baromfitartó gazdaságokban Magyarországon - Bartl, Bianka; Ábel, Ildikó (GEORGIKON FOR AGRICULTURE, 2020)
The authors based the data of the Test Plant System (FADN) operated by the Agriculture Research Institute (at the following AKI) on the structure of investments in poultry farms. The period under review: 2005-2017. We made a distinction between small, medium and large plant sizes and we examined, with the data of these farms separately. Significant differences can be observed in all of the indicators examined, with the most significant ones being seen in terms of grants and net investment. The volume and distribution of investment subsidies and net investment were influenced by the characteristics of size of the plant. While the volume of gross investment is the highest for the small ones this order revolves around subsidies and net investment. Regarding the structure of gross investment, the largest value for all three farm size was recorded for breeding animals, whereas in case of real estate we experienced changes per plant size.
Keywords: poultry indurstry; gross investment; investment aid; net investment